Who can enjoy the unavoidable emotional labor: A moderation of self-monitoring - Baeck, SeungGeun; Shin, KangHyun; Lee, JongHyun; Heo, ChangGoo (Korean Journal of Industrial and Organizational Psychology, 2014)
The purpose of this study was to examine the positive effect of self-monitoring among emotional display rules (fostering positive emotion(FPE) & suppressing negative emotion(SNE)) and consequential work attitude (job burnout & work engagement). A sample of 191 hotel employees were participated in this study and data were analyzed by SPSS. The results are as follows. First, the main effect of FPE on work engagement was supported, but the main effect of SNE on job burnout was not. Second, the main effects of self-monitoring on engagement and burnout were supported. Third, the moderation effects of self-monitoring which buffer the relationship of SNE on burnout and which facilitate the relationship FPE on engagement were significant. Finally, the implications and limitations were discussed.